Neural network based on adaptive resonance theory with continuous training for multi-configuration transient stability analysis of electric power systems - Marchiori, Sandra C. [UNESP]; da Silveira, Maria do Carmo G. [UNESP]; Lotufo, Anna Diva P. [UNESP]; Minussi, Carlos R. [UNESP]; Martins Lopes, Mara Lucia [UNESP] (Elsevier B.V., 2011)
This work presents a methodology to analyze electric power systems transient stability for first swing using a neural network based on adaptive resonance theory (ART) architecture, called Euclidean ARTMAP neural network. The ART architectures present plasticity and stability characteristics, which are very important for the training and to execute the analysis in a fast way. The Euclidean ARTMAP version provides more accurate and faster solutions, when compared to the fuzzy ARTMAP configuration. Three steps are necessary for the network working, training, analysis and continuous training. The training step requires much effort (processing) while the analysis is effectuated almost without computational effort. The proposed network allows approaching several topologies of the electric system at the same time; therefore it is an alternative for real time transient stability of electric power systems. To illustrate the proposed neural network an application is presented for a multi-machine electric power systems composed of 10 synchronous machines, 45 buses and 73 transmission lines. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Electric power systems; Transient stability analysis; Neural network; Euclidean ARTMAP neural network